PRODUCTIVITY AND QUALITY OF SOFT WINTER WHEAT VARIETIES IN THE EASTERN PART OF THE ROSTOV REGION - A. S. Popov (Зерновое хозяйство России, 2018)
The choice of the variety is one of the main methods of soft winter wheat productivity increase. The trials have been carried out by the staff of the laboratory of crop cultivation technologies in the Orlovsky region in the eastern part of the Rostov region on the experimental fields of OOO ‘Niva’. The experimental plot was of dark-chestnut soil of medium capacity and with weak alkalinity. According to the texture, heavy loam soils with the content of physical clay of 60-75% contain average phosphorus and potassium. The content of humus in the layer of 0-20 cm is between 2,5-3,1%. The objects of study were the varieties of soft winter wheat of FSBSI ARRIGC named after I.G. Kalinenko. They are ‘Rostovchanka 3’, ‘Rostovchanka 5’, ‘Don 107’, ‘Stanichnaya’, ‘Tanais’, ‘Ermak’, ‘Asket’, ‘Izyuminka’, ‘Donskoy Surpriz’, ‘Lidiya’ and ‘Nakhodka’. The study was carried out in the years 2012-2014 which were different in moisture supply. The year 2012-2013 was dry, but the year 2013-2014 was the most favorable due to amount of precipitations, therefore the productivity of the crop varied in these years. On average the largest productivity have been produced by such varieties as ‘Rostovchanka 5’(3,37 t/ha), ‘Stanichnaya’(3,37 t/ha), ‘Tanais’(3,31 t/ha), ‘Ermak’(3,38 t/ha), ‘Asket’(3,50 t/ha), ‘Izyuminka’(3,38 t/ha), ‘Donskoy Surpriz’(3,33 t/ha), ‘Lidiya’(3,63 t/ha) and ‘Nakhodka’(3,39 t/ha). The variety ‘Asket’ showed the most amount of protein (15,6%) and gluten (34,6%) on average during the years of study. The varieties ‘Don 107’ (749 g/l) and ‘Izyuminka’ (748 g/l) showed the best quality of grain.